Analisis Praktik Manajemen Rantai Pasokan pada UMKM Makanan dan Minuman di Purwokerto - Triwibowo, Rony Nur; Noegroho, Asharryadi (ICON Publisher, 2025)
. The purpose of this study was to determine whether supply chain management has a practical effect on the performance of food and beverage MSMEs in Purwokerto. The research sample consisted of 100 MSME actors. Sample collection used an online questionnaire. The analysis used in this study used Smart PLS 3.0. The results stated that SCMP did not have a direct positive effect on MSME performance, but it positively affected digital adaptation. Digital Adaptation did not significantly affect MSME performance or mediate the relationship between SCMP and MSME performance. The limitation of this study is that the scope of this study is limited to food and beverage MSMEs in Purwokerto, which may affect the ability to generalize the findings to other sectors or regions with different characteristics. Theoretically, this study contributes to the existing literature by challenging the alleged positive relationship between SCMP, Digital Adaptation, and MSME performance. Practically, these findings indicate that MSMEs should not assume that implementing SCMP and adopting digital technology will automatically improve performance. Further research is recommended to use a broader and more diverse sample across industries and regions to improve the generalization of findings.